Analisis Perpindahan Kanal Komunikasi dalam Satu BSC pada Sistem GSM Berdasarkan Data Drive Test Menggunakan TEMS Investigation 4.1.1 - Luluk Arifatul Chalida; Imam Santoso; Yuli Christyono (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
Mobile communications system created to meet the communication needs that can be done anywhere either when user is motionless or moving. To maintain the quality of services in a wide service area, coverage area is divided into smallest geographic units called cells. If the user moves from one area of the cell to another, then it needs an algorithm that guarantees the continuity of communications services. These algorithm is called a handover to a dedicated mode and the cell reselection for idle mode. In observing handoff algorithm, the operator did a drive test using computer and handset, which each had been equipped with special software, and GPS. This research analyze the problems related to the handoff algorithm, both when in idle mode or dedicated mode, including the causes, processes and things that influence it. Data acquisition is carried out through a drive test using software TEMS Investigaions GSM 4.1.1 with routes in the downtown area of Semarang. Drive test held on every Thursday and Sunday for three consecutive weeks starting on August 23, 2009 and each of day divided into three time allocation, ie morning, noon and night. The observed event include: cell reselection, handover, handover (intracell), handover failure and intracell handover failure. In addition Information Element that effected on the event are also observed, path loss criteria and cell reselection criteria for cell reselection, and received power, bit error rate and timing advance for the four other events. From the analysis is known that the assignment channel is triggered by the Information Element value that reaches a certain threshold value. For cell reselection, the both Information Element having equal influence. Information Element of the most influential for the handover and the handover failure is received power, whereas for two other events the most influential is the received bit error. After the detected value of the Information Element reaches a certain threshold, MSC will instruct the candidate cell to monitor and serving mobile station. Different process going on for handover (intracell), which after the information element value is known at a certain threshold, MS will move to another traffic channel in the same cell. If handover (intracell) was requested but could not be performed then handover based quality is tried the next time (if criterion is still given). When this handover also fails then BS toggles back and tries again a handover (intracell). In this drive test result there are 15 handover failures that may because no available traffic channel in candidate cell. There is only once handover intracell failure happened which may be caused by full traffic in candidate channel, but no cell reselection failure is found because this event doesn’t need traffic channel but only signaling channel. Keywords: handover, cell reselection, intracell, IE, TEMS